2018
DOI: 10.1016/j.jpcs.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sodium cobaltate NaxCoO2 single crystals with controlled Na ordering

Abstract: In this study, we synthesized single crystals of Na x CoO 2 with x ~ 0.8 using the optical floating zone technique. A thorough electrochemical treatment of the samples permitted us to control the de-intercalation of Na to obtain single crystal samples of stable Na ordered phases with x = 0.5-0.8. Comparisons of the bulk magnetic properties with those observed in the Na ordered powder samples confirmed the high quality of these single crystal phases. The ab plane resistivity was measured for the Na ordered samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Tanaka et al [134] showed that polycrystalline NaCo 2 O 4 is a good metal at temperatures up to 12 K, and demonstrates the Curie-Weiss magnetic susceptibility, instead of Pauli paramagnetism typical for metals. Gilmutdinov et al [135] synthesized single crystals of Na x CoO 2 with x ∼ 0.8 using the method of optical floating zones. Thorough electrochemical processing of the samples made it possible to control Na deintercalation and obtain single-crystal samples of stable ordered Na phases with x = 0.5-0.8.…”
Section: Layered Oxides Naxcoomentioning
confidence: 99%
“…Tanaka et al [134] showed that polycrystalline NaCo 2 O 4 is a good metal at temperatures up to 12 K, and demonstrates the Curie-Weiss magnetic susceptibility, instead of Pauli paramagnetism typical for metals. Gilmutdinov et al [135] synthesized single crystals of Na x CoO 2 with x ∼ 0.8 using the method of optical floating zones. Thorough electrochemical processing of the samples made it possible to control Na deintercalation and obtain single-crystal samples of stable ordered Na phases with x = 0.5-0.8.…”
Section: Layered Oxides Naxcoomentioning
confidence: 99%
“…If one compares the behavior of the Hall effect with that of the resistivity one can see on Fig. 6 that the onset of the low T decrease of the Hall effect coincides with the onset of a decrease of dρ/dT which indicates an inflexion point at about 30 K which has also been found quite reproducible (17). We might notice as well that the change of behavior of the Hall effect is concomitant with the large increase of the spin susceptibility detected by NMR without any onset of magnetic order down to T=0 (34).…”
Section: X=2/3 Kagome Like Phasementioning
confidence: 73%
“…Subsequent electrochemical treatment was used in order to decrease sodium content and to obtain crystals with homogeneous sodium distribution. Details of the sample preparation techniques and samples control have been described elsewhere (17).…”
Section: Appendix a : Samples And Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This excess of Na 2 CO 3 in the starting mixture compensates for the Na 2 O loss during the high temperature heat treatment. In another work, 43 NaCoO 2 was synthesized from the same reactants, but using a procedure in which the powder mixture was grinded manually in an agate mortar for 2 h, then loaded into an alumina crucible and subsequently sintered three times at 860 °C in air. In such synthesis procedure, intermediate grinding was performed in a moisture-free atmosphere inside a glove box to obtain an homogeneous composition.…”
Section: Resultsmentioning
confidence: 99%